Avoid Drug Incompatibilities: Clinical Context in Neonatal Intensive Care Unit (NICU) - Flamein Florence (Pharmaceutical Technology in Hospital Pharmacy, 2017)
The administration of several intravenous products on the same catheter is a very common situation in neonatology, where the stakes are high and the dangers sometimes unknown to clinicians. A large number of factors are involved in this administration, directly related to the installation of the infusion line. Moreover, the therapeutics used are often limited, and excluding classic “Marketing Authorization”. Some of these products may prove to be incompatible and thus lose their effectiveness, or even generate particles that are likely to be administered to the patient. We must be aware of these risks in order to optimize the prescription and administration of these intravenous products, especially as we treat fragile and immature patients. The aim of this work is to review the literature on the subject for the prescribers of neonatology units.